Resistance to Gender Norms in Sayaka Murata’s Convenience Store Woman: A Feminist Analysis of Women’s Roles in Japan’s Patriarchal Society - Regita Sekar Arrum; Dindadari Arum Jati (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This study examines resistance to gender norms in Sayaka Murata’s Convenience Store Woman through a feminist literary perspective. This study focuses on the representation of women’s roles within Japan’s patriarchal society where social expectations surrounding marriage, career, and femininity strongly shape women’s identities. This research employs a qualitative method using feminist literary criticism by Judith Butler about Gender Performativity. The analysis explores the narrative strategies and the characters in reinforcing feminist discourse within the context of modern Japan. The findings reveals that the main character, Keiko Furukura, is portrayed as a form of resistance to the dominant gender norm in Japan. Her rejection of conventional life trajectories such as marriage and corporate success destabilizes hegemonic ideals of femininity and exposes the constraints imposed by patriarchal values. Through its characters and narrative strategies, the novel also advances a feminist critique by revealing patriarchal values that marginalize women. Ultimately, this study demonstrates that Convenience Store Woman articulates a subtle yet powerful feminist critique by foregrounding nonconformity as a form of resistance. This study also reveal that the novel redefines female autonomy beyond socially imposed ideals of womanhood.